The relationship between personality, self-efficacy and students' academic achievement in Dolok Merawan sub-district - Wulandari, Rizki (Kulliyyah of Education, International Islamic University Malaysia, 2014)
The primary objective of the present study is to examine the relationship between personality, self-efficacy and academic achievement of senior high school students in Dolok Merawan sub-district, North Sumatera Indonesia. It further attempts to find out the most common personality among senior high school students. It also investigates the students' level of self-efficacy. The present study used Big Five Inventory questionnaire by John and Srivasta (1999) to measure students' personality and a modified academic self-efficacy by Landry (2003) to measure students' level of self-efficacy. The questionnaire was distibuted to 100 senior high students. Descriptive and inferential statistics were used in this study. Pearson Product Moment Correlation was applied to examine the correlation between variables. The present study found that out of 100 students, the majority agreed with openness statements with percentages ranging from 45% - 90%. Therefore, the majority of senior high school students in Dolok Merawan sub-district were regarded as having openness personality type. Next, it is reported in the findings that the level of self-efficacy among these senior high students was very high. Out of 100 respondents in this study, the majority of respondents agreed with the statements in the questionnaire with large percentages between 83% - 99%. But this finding is not similar to the finding on the relationship between self-efficacy and students' academic achievement. The finding shows that there was no relationship between self-efficacy and students' academic achievement. Lastly, the present study found that out of five personality types, a relationship was only found between openness and academic achievement, whereas the other four personality types did not have any relationship with students' academic achievement.